2010
DOI: 10.4314/ajns.v27i2.55100
|View full text |Cite
|
Sign up to set email alerts
|

Prise en charge du spondylolisthesis par lyse isthmique a niamey, a propos de 20 cas

Abstract: RESUME Objectif Evaluer la prise en charge chirurgicale du spondylolisthésis par lyse isthmique à Niamey. Méthode Etude prospective en série continue réalisée dans le service de Neurochirurgie de Niamey de Janvier 1999 à Janvier 2006. Etaient inclus les spondylolisthésis par lyse isthmique. Les spondylolisthésis étaient classés selon la classification de Meyerding. L'indication opératoire était retenue après échec du traitement conservateur sur les radiculalgies. L'évaluation clinique préopératoire et post opé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…The mean age of our patients was 52.3±10.9 years. This age was 55.9±14.5 years according to Schoenfield et al [25], 53.1±17.5 years according to Péreira et al [21], 51.47 years according to Sanoussi et al [9] and 57.3 years according to Djientcheu et al [5]. All these authors, like others [4,15], have not found a correlation between the age of the patients and the occurrence of post-operative complications.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The mean age of our patients was 52.3±10.9 years. This age was 55.9±14.5 years according to Schoenfield et al [25], 53.1±17.5 years according to Péreira et al [21], 51.47 years according to Sanoussi et al [9] and 57.3 years according to Djientcheu et al [5]. All these authors, like others [4,15], have not found a correlation between the age of the patients and the occurrence of post-operative complications.…”
Section: Discussionmentioning
confidence: 82%
“…It also contributes to a better pre-operative assessment of the risks, a good selection of patients, and finally a reduction in the mortality and morbidity of this surgery [10,20,21,24,25]. Like several authors before us [9,10,14,15], by performing this study over a long period and with a large sample size, we are performing a self-assessment of the practice of degenerative spinal surgery in Parakou (Benin). There are two types of post-operative morbidity associated with lumbar canal stenosis: Surgical morbidity and morbidity due to the health condition of the patient him/herself and the problems regarding operating environment [19,26].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations